Association of Pain Centralization and Patient‐Reported Pain in Active Rheumatoid Arthritis. Issue 8 (21st July 2020) - Heisler, Andrew C.; Song, Jing; Dunlop, Dorothy D.; Wohlfahrt, Alyssa; Bingham, Clifton O.; Bolster, Marcy B.; Clauw, Daniel J.; Marder, Wendy; Phillips, Kristine; Neogi, Tuhina; Lee, Yvonne C.
Abstract : Objective: Pain is a significant burden for patients with rheumatoid arthritis (RA) despite advancements in treatment. We undertook this study to examine the independent contribution of pain centralization to the pain experience of patients with active RA. Methods: A total of 263 RA patients with active disease underwent quantitative sensory testing (QST), including assessment of extraarticular pressure pain thresholds (PPTs), temporal summation (TS), and conditioned pain modulation (CPM). The pain experience was assessed by a pain intensity numeric rating scale and the Patient‐Reported Outcomes Measurement Information System pain interference computerized adaptive test. We examined associations between QST measures and pain intensity and pain interference. Multiple linear regression models were adjusted for demographic and clinical variables, including swollen joint count and C‐reactive protein level. Results: Patients with the lowest PPTs (most central dysregulation) reported higher pain intensity than patients with the highest PPTs (adjusted mean difference 1.02 [95% confidence interval (95% CI) 0.37, 1.67]). Patients with the highest TS (most central dysregulation) had higher pain intensity than those with the lowest TS (adjusted mean difference 1.19 [95% CI 0.54, 1.84]). CPM was not associated with differences in pain intensity. PPT and TS were not associated with pain interference. Patients with the lowest CPM (most centrally dysregulated) had lower pain interference than patients with the highest CPM (adjusted mean difference −2.35 [95% CI −4.25, −0.44]). Conclusion: Pain centralization, manifested by low PPTs and high TS, was associated with more intense pain. Clinicians should consider pain centralization as a contributor to pain intensity, independent of inflammation.